2021
DOI: 10.7759/cureus.18114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Admission Chest X-Ray Findings in Patients With Respiratory Infection During the COVID-19 Pandemic

Abstract: Aims: To evaluate the prevalence of X-ray findings in hospitalized patients requiring hospitalization with suspected Coronavirus disease 2019 (COVID-19) infection and potential differences in the laboratory values and clinical outcomes related to the presence of abnormal chest X-ray (CXR) findings.Methods: A total of 117 patients suspected of COVID-19 pneumonia and hospitalized with symptoms of lower respiratory tract disease were included in this study. Patients were divided into subgroups according to COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Other authors [20], by enrolling 117 patients suspected of SARS-CoV-2 pneumonia and hospitalized with lower respiratory tract symptoms, demonstrated that CXR findings were significantly more evident in patients affected with COVID-19 when compared with the non-COVID-19 group (83 vs. 42%, p < 0.001). Moreover, the authors reported that CXR abnormalities observed during admission could be considered as predictors for prognosis; patients with abnormal CXR findings reported significantly higher mortality (p = 0.0014).…”
Section: Chest X-ray (Cxr)mentioning
confidence: 99%
“…Other authors [20], by enrolling 117 patients suspected of SARS-CoV-2 pneumonia and hospitalized with lower respiratory tract symptoms, demonstrated that CXR findings were significantly more evident in patients affected with COVID-19 when compared with the non-COVID-19 group (83 vs. 42%, p < 0.001). Moreover, the authors reported that CXR abnormalities observed during admission could be considered as predictors for prognosis; patients with abnormal CXR findings reported significantly higher mortality (p = 0.0014).…”
Section: Chest X-ray (Cxr)mentioning
confidence: 99%
“…In established clinical practice, the presence of chest X-ray (CXR) abnormalities provides radiological confirmation of pneumonia [ 8 ], which is also an independent risk factor for adverse clinical outcomes in COVID-19 patients [ 9 , 10 , 11 , 12 ]. Whilst CXR findings such as ground glass changes and consolidation are common in acute COVID-19 patients, a significant proportion of patients can also present with normal CXRs [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%